In vitro study of fungal presence and growth on three tissue conditioner materials. - (:unkn) unknown (My University, 1997)
In this study three type of tissue conditioning materials (Visco-gel, Fixo-gel, Fitt) are used in vitro to investigate the presence and growth of Candida albicans. In vitro test results of different tissue conditioners showed no inhibiting effect on Candida albicans.